The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.inorgchem.1c03958
|View full text |Cite
|
Sign up to set email alerts
|

Silver(I)-Based Molecular Perovskite Energetic Compounds with Exceptional Thermal Stability and Energetic Performance

Abstract: In recent years, molecular perovskite energetic materials have attracted more attention because of their simple synthesis processes, high thermal stabilities, excellent performances, and great significance as a design platform for energetic materials. To explore the possibility of the application of molecular perovskite energetic materials in heat-resistant explosives, four silver­(I)-based molecular perovskite energetic compounds, (H2A)­[Ag­(ClO4)3], where H2A = piperazine-1,4-diium (H2pz2+) for PAP-5, 1-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…For instance, by changing the A-site components from H 2 dabco 2+ to other organic cations with trimmed C and H atoms or adding O atoms, the oxygen balance parameter and detonation performances could be improved [29,30]. By using silver(I) ions or derivatives of NH ) to serve as the B-site cation, we attained four new silver(I) perchlorate perovskites as potential heat-resistant primary explosives [31] and two metal-free hexagonal perovskite energetic crystals with detonation performances surpassing DAP-4 [32]. Very recently, by using nitrate ions as the X-site bridges, we obtained a nitratebased energetic molecular perovskite as a modern edition of black powder with promising application potentials in the field of gunpowder and pyrotechnics [33].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, by changing the A-site components from H 2 dabco 2+ to other organic cations with trimmed C and H atoms or adding O atoms, the oxygen balance parameter and detonation performances could be improved [29,30]. By using silver(I) ions or derivatives of NH ) to serve as the B-site cation, we attained four new silver(I) perchlorate perovskites as potential heat-resistant primary explosives [31] and two metal-free hexagonal perovskite energetic crystals with detonation performances surpassing DAP-4 [32]. Very recently, by using nitrate ions as the X-site bridges, we obtained a nitratebased energetic molecular perovskite as a modern edition of black powder with promising application potentials in the field of gunpowder and pyrotechnics [33].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary experimental results showed that (C 6 H 14 N 2 )NH 4 (ClO 4 ) 3 (DAP-4) in molecular perovskite-type energetic materials had a significant catalytic effect on the burning rate of composite modified double-base propellant. In the pressure range of 1–22 MPa, the burning rate at different pressures was basically increased, especially at high pressure (10–22 MPa), the burning rate was greatly increased ( Shang et al, 2022 ; Shang et al, 2020a ; Shang et al, 2020b ; Chen et al,2018a ; Chen et al, 2022 ; Zhang J. et al, 2020 ).…”
Section: Catalysts That Can Be Compounded With Emofsmentioning
confidence: 95%
“…), such as the reported [Co(N 3 ) 2 (atrz)] n (named CoATRZ, atrz = 4,4′-azo-1,2,4-triazole), 3 [Cu 3 (2-MAT) 2 (N 3 ) 6 ] n (named CMA), 22 {[Co(NH 2 NH 2 ) 5 ](ClO 4 ) 2 } n (named CHP), 23 and (H 2 A)[Ag(ClO 4 ) 3 ] (named PAP-5, H 2 A = piperazine-1,4-diium). 24 Three-component ECPs exhibit enhanced detonation properties. However, the sensitivities of ECPs based on ClO 4 − or N 3 − anions are always very high, which greatly limits their applications.…”
Section: Introductionmentioning
confidence: 99%